Non-pharmacological Management in Palliative Care for Patients With Advanced COPD - Pyszora, Anna; Lewko, Agnieszka (Frontiers in Cardiovascular Medicine, 2022)
Chronic obstructive pulmonary disease (COPD) is a disabling condition associated with progressive airflow limitation and lung tissue damage; its main symptoms are breathlessness, fatigue, cough, and sputum production. In the advanced stage of the disease, these symptoms may severely impact on a person's physical and psychological functioning, with some also developing chronic respiratory failure, associated with blood gas abnormalities. Non-pharmacological interventions can improve quality of life and functioning in the management of people living with advanced COPD. This article will provide an overview of common non-pharmacological methods used in the symptomatic management of severe COPD, including: breathlessness and fatigue management strategies, anxiety management, pulmonary rehabilitation (PR) and physical activity (PA), neuromuscular electrical stimulation (NMES), airway clearance techniques (ACTs), nutrition and non-invasive ventilation (NIV). The importance of a holistic and multi-disciplinary approach to people living with COPD will be discussed.